History of Microfilms in Helsinki University Library / National Library of Finland - Sorjonnen, Maria (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
The Helsinki University Library started the microfilming of Finnish newspapers in 1951 on 35 mm safety film which was cellulose acetate based until the last half of the 1980’s. After some preliminary projects a private service bureau called Rekolid both filmed and copied the films. Because of many kinds of problems the filming was given to Helsinki University Photographic Institute, later known as Helsinki University Audio-Visual Centre, where they also had more interest in the theoretical aspects of photography. The Institute had some scientific research activities too. The technical quality of the microfilms rose when the existing standards were introduced and taken seriously, test targets were utilized, the densities were checked with a properly calibrated densitometer, and so on. The next change took place in 1990 when Helsinki University established the Centre for Microfilming and Conservation in Mikkeli some 230 kilometres northeast of Helsinki. Finally in 1999 The Audio-Visual Centre was closed down and the Microfilming Unit was integrated into the library. When everybody else was outsourcing activities newspaper microfilming was taken up in-house and this was a good decision. We can concentrate more on quality matters than before, and take into account the needs of digitisation and OCR. Economy is not the fundamental basis for actions even though it is still an important aspect.